HUBUNGAN POLA TIDUR DENGAN TEKANAN DARAH PADA SISWA SMA N 2 BOYOLALI - Emy Kurniawati; Ika Purnamasari (STIKES Estu Utomo, 2024)
Background: The sleeping habit is a human physiological system to rest the body for a current time to find and improve body systems. Blood pressure is the pressure that comes from the flow of blood in the blood vessels that occurs when blood pressure is throughout the body. Adolescence is a period of transition from childhood to adulthood. Adolescents with poor sleep patterns can have abnormal sleep patterns, the heart muscle will be tired then there may be thickening of the heart muscle. Objective: This study was conducted to determine the relationship between sleep patterns and blood pressure in students of SMA N 2 Boyolali. Methods: This study uses a quantitative type design with a correlation analytic method with a Cross-Sectional design. The sampling technique used is probability sampling with a stratified random sampling technique, namely random samples with 75 respondents, the data collection by questionnaire, and blood pressure measurement. The analysis used the chi-square test. Result: Based on the chi-square test, the p-value 0,000 < ? 0,05 means that H0 is rejected and Ha is accepted. That is, there is a relationship between sleep patterns and blood pressure in SMA N 2 Boyolali students. Conclusion: There is a relationship between sleep patterns and blood pressure in SMA N 2 Boyolali student.